Use of the results of the work of the ukrainian meteor network in the process of teaching physics to students of the educational and scientific institute of energy, automation and energy saving NULES of Ukraine - Hrudynin, B. (Energy and Automation, 2023)
Features of meteor fixation methods are presented by organizing a network of corresponding observation points - permanently operating observation stations located on the territory of Ukraine with appropriate technical and software support for conducting basic and one-way observations of meteors in the radio range of electromagnetic wavelengths. This contributes to solving the strategic problems of meteor research, the structure and evolution of meteor showers and streams, the interaction of meteoroids with the Earth's atmosphere and their chemical composition. Scientific and technical products of observation stations are the results of high-precision basic or one-sided observations of meteors in the radio range of electromagnetic wavelengths, fundamental and applied scientific and technical research.The purpose of the study is to consider the principle of operation of the Ukrainian meteor observation network, a separate meteor hardware and software complex for observing meteors in the radio range of electromagnetic waves using the method of direct scattering on meteor trails of signals from powerful FM radio broadcasting stations with the possibility of further processing and presentation of data by students of specialties 141 "Electric power, electrical engineering and electromechanics", 144 "Thermal power engineering", 174 "Automation, computer-integrated technologies and robotics" of the Educational and Scientific Institute of Energy, Automation and Energy Saving of NULES of Ukraine in the process of studying physics.Processing of experimental data was carried out by students of the specified specialties under the guidance of the author while studying physics.The results of statistical data processing of meteor invasions and their graphic representation by students of the specified specialties in the process of mastering physics are described.Prospects - putting into operation by the end of 2024 the seventh receiving station in the city of Kyiv (student campus of NULES of Ukraine) - the seventh meteor hardware and software complex, as a component of the Ukrainian meteor observation network.Key words: meteor, meteor stream, Ukrainian meteor observation network, meteor hardware and software complex